Lumbosacral Sagittal Alignment in Association to Intervertebral Disc Diseases - Zohreh Habibi; Farid Maleki; Ali Tayebi Meybodi; Ali Mahdavi; Hooshang Saberi (Asian Spine Journal, 2014)
Study DesignA cross-sectional case-control study was designed to compare the sagittal alignment of lumbosacral regions in two groups of patients suffering from low back pain, one with intervertebral disc pathologies and one without.PurposeTo evaluate the correlation between lumbosacral sagittal alignment and disc degeneration.Overview of LiteratureChanges in lumbar lordosis and pelvic parameters in degenerative disc lesions have been assessed in few studies. Overall, patients with discopathy were shown to have lower lumbar lordosis and more vertical sacral profiles.MethodsFrom patients with intractable low back pain undergoing lumbosacral magnetic resonance imaging, 50 subjects with disc degeneration and 50 controls with normal scans were consecutively enrolled. A method was defined with anterior tangent-lines going through anterior bodies of L1 and S1 to measure global lumbosacral angle, incorporating both lumbar lordosis and sacral slope. Global lumbosacral angle using the proposed method and lumbar lordosis using Cobb's method were measured in both groups.ResultsLumbar lordosis based on Cobb's method was lower in group with discopathy (20°-67°; mean, 40.48°±9.89°) than control group (30°-62°; mean, 44.96°±7.68°), although it was not statistically significant. The proposed global lumbosacral angle in subject group (53°-103°; mean, 76.5°±11.018°) was less than control group (52°-101°; mean, 80.18°±9.95°), with the difference being statistically significant (p=0.002).ConclusionsPatients with intervertebral disc lesions seem to have more straightened lumbosacral profiles, but it has not been proven which comes first: disc degeneration or changes in sagittal alignment. Finding an answer to this dilemma demands more comprehensive long-term prospective studies.